Cosmogonic Views Of The Uzbek People (Based On The Example Of Southern Uzbekistan) - F. Sh. Rakhmonov (Zien Journals, 2024)
In this article, based on available sources, literature and field materials, traces of ancient beliefs in the national cosmogonic views of the Uzbek people are highlighted
Keywords: Sky; moon; sun; star